Religious Habituation Policy Implementation in an Islamic Elementary School: An Edward III Model Analysis - Mushalipah; Encep Hidayat; Dini Permana Sari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The implementation of religious habituation programs in Madrasah Ibtidaiyah plays a vital role in fostering a religious culture, yet it frequently encounters structural and cultural challenges. This study analyzes the implementation of such policies at MI Daarul Uluum South Jakarta, a community-based urban madrasah characterized by heterogeneous student backgrounds, using George C. Edward III's policy implementation model. A qualitative case study approach was employed. Data were collected over a three-month observation period through in-depth semi-structured interviews with eight key informants comprising the headmaster, three classroom and Islamic Religious Education (IRE) teachers, two administrative staff members, and two senior students complemented by direct participant observation of daily religious activities, and a documentation study of the school curriculum, activity schedules, attendance logs, and institutional records. The absence of formal Standard Operating Procedures (SOPs) was confirmed through document analysis. Data were analyzed using the Miles and Huberman interactive model. The findings show that program implementation is supported by strong teacher dispositions and informal resource mechanisms, particularly the culture of ta'awun (mutual assistance) and gotong royong (communal cooperation). However, several structural constraints persist: communication is dominated by an 'oral culture' that lacks the stability of formal documentation; resource limitations, particularly in prayer-space infrastructure, are partially compensated by social capital; and the absence of SOPs results in subjective, intuitive evaluation rather than systematic, indicator-based character assessment. Critically, the study reveals that implementation tends to produce compliance-based moral behavior ('adah) rather than deep value internalization (malakah), particularly when direct supervision is absent. The central theoretical contribution lies in characterizing MI Daarul Uluum's implementation pattern as 'Actor-Centric Resilience' a mode in which institutional continuity is sustained primarily through the spiritual commitment of individual implementers rather than through formal governance systems. The study recommends the formalization of archival governance through written SOPs, competency-based character assessment rubrics, and structured parent-school communication mechanisms to ensure long-term program sustainability and accountability.